PERSEPSI SISWA KELAS X SMAN 1 PALIMANAN TERHADAP PEMBELAJARAN PENDIDIKAN JASMANI - Haryati; Andrie Chaerul; Setio Nugroho (Jurnal Speed (Sport, Physical Education, Empowerment), 2021)
ABSTRACT The purpose of this research is motivated by the lack of interest of students in learning Physical Education and because of the coercion in learning Physical Education. This study aims to determine the perceptions of class X students at SMAN 1 Palimanan on physical education learning. This research is a descriptive quantitative research, the method used is a survey. with data collection techniques using a questionnaire using a test question statement. The population in this study amounted to 36 students of class X at SMAN 1 Palimanan. The sample used in this study was 36 students with a sampling technique (total sampling). The results showed 58% of students' perceptions of physical education learning at SMAN 1 Palimanan as a whole were in the "Good Enough" category. Keywords: Student perceptions, learning, physical education